The Effectiveness of Online Counselling Program Based on the Acceptance and Commitment to Improve Post-Traumatic Growth among Females Recovered from Corona Virus Disease (Covid-19): An Experimental study in Jeddah - Al-Sofyani, Hanan Hamed; Al-Rfei, Yahya Abdallah (Journal of Educational and Psychological Sciences, 2023)
This study aims to recognize the effectiveness of online counselling program based on the acceptance and commitment to improve the level of post-traumatic development among females recovered from Corona Virus Disease (COVID-19) in Jeddah. Sample group of the study was composed of 24 female nurses recovered from COVID-19، whose age group ranged between 31 and 41 years old with an overall average of 39.79 and Standard Deviation of 3.006. The Sample Group was divided into standard and empirical subgroups (where each and every subgroup was composed of 12 nurses). The researcher employed the post-traumatic development scale، together with a questionnaire of acceptance and work، another questionnaire for cognitive integration، a questionnaire for valuable life (translated by the researcher)، a questionnaire of mental diligence (translated by Radwan and El-Sayed، 2021)، an online counseling program based on the acceptance and commitment to improve the level of post-traumatic development among female nurses recovered from COVID-19 in Jeddah (developed by the researcher). To this aim، the researcher employed the quasi-empirical methodology with empirical design of two subgroups: empirical and standard; and pre-، post- and consecutive measurement، in addition to the correlative descriptive approach. The study concluded statistically indicated differences between average marks of empirical subgroups on one hand and average marks of standard subgroups on the post-traumatic development scale in the post-measurement in favor of the empirical subgroup. Also، findings of the study pointed at statistically indicated differences between averages of pre- and post-measurements for the empirical subgroup on the post-traumatic development scale in favor of the post-measurement. No statistically indicated differences were detected among average marks of empirical subgroup in post-traumatic development between consecutive- and post-measurement. Similarly، no statistically indicated differences were found among average marks of the standard subgroup in post-traumatic development between consecutive- and post-measurement. Findings of the study were discussed in the light of literature review. Accordingly، a number of recommendations were made.